Coefficient Estimates for New Subclasses of Bi-Univalent Functions Associated with Jacobi Polynomials (Contemporary Mathematics, 2024)
Our research introduces new subclasses of analytical functions that are defined by Jacobi polynomials. We then proceed to estimate the Fekete-Szegö functional problem and the Maclaurin coefficients for this specific subfamily, denoted as |a2| and |a3|. Furthermore, we demonstrate several new results that emerge when we specialize the parameters used in our main findings.
Keywords: analytic functions, univalent functions, bi-univalent functions, Jacobi polynomials, fekete-szegö problem